2019
DOI: 10.3382/ps/pez452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of autolyzed whole yeast and yeast components on broiler chickens challenged with salmonella lipopolysaccharide

Abstract: The objective of this study was to assess the effect of dietary yeast products on broiler chickens challenged with salmonella lipopolysaccharide (LPS). The chicks were divided into 8 treatments with 6 replicates and 9 birds per replicate. The treatments consisted of a positive control (PC) [without supplementation and not challenged]; negative control (NC) [without supplementation but challenged]; whole yeast and challenged; yeast cell wall and challenged; yeast glucan and challenged; yeast mannan and challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
(37 reference statements)
4
16
1
Order By: Relevance
“…Inconsistence with our finding, results from a study (Van Der Peet-Schwering, Jansman, & Smidt, 2007) showed that yeasts products can lowered the levels of neutrophils in the blood of piglets. Our finding is agreement with the report of Ahiwe et al (2019) who reported dietary supplementation of chickens with whole yeast, yeast cell wall, yeast glucan, and yeast mannan led to decrease (p < 0.05) in lymphocyte and Acta Scientiarum. Animal Sciences, v. 42, e48425, 2020 increase in neutrophil.…”
Section: Treatmentsupporting
confidence: 93%
“…Inconsistence with our finding, results from a study (Van Der Peet-Schwering, Jansman, & Smidt, 2007) showed that yeasts products can lowered the levels of neutrophils in the blood of piglets. Our finding is agreement with the report of Ahiwe et al (2019) who reported dietary supplementation of chickens with whole yeast, yeast cell wall, yeast glucan, and yeast mannan led to decrease (p < 0.05) in lymphocyte and Acta Scientiarum. Animal Sciences, v. 42, e48425, 2020 increase in neutrophil.…”
Section: Treatmentsupporting
confidence: 93%
“…Comparing unchallenged versus challenged groups, the relative spleen weight was observed to be significantly higher among birds in the latter compared to the former. According to Ahiwe et al. (2019) , increased spleen weight was reported in broiler chickens challenged with Salmonella Typhimurium LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria impaired gut function, shifted gut microbiome and performance; yeast nucleotides improved performance independently, attenuated Eimeria damage on indices of gut function and modulated caecal microbiome. In the study of (Ahiwe et al ) reported that whole yeast and its derivatives can improve meat yield of broilers and through its effect on white blood cell, lymphocyte and monocyte counts, may be linked to an amelioration of stress induced by Salmonella lipopolysaccharide in broilers. They also noted that autolysed yeast, yeast cell wall and its enzymatically hydrolysed components when supplemented at 2 g kg −1 diet may act as an appropriate alternative to antibiotics in broilers production.…”
Section: Probiotic Yeast For Poultrymentioning
confidence: 99%